Layered SnSe nano-plates with excellent in-plane anisotropic properties of Raman spectrum and photo-response. Issue 38 (21st September 2017) - Li, Xuan-Ze; Xia, Jing; Wang, Lei; Gu, Yi-Yi; Cheng, Hua-Qiu; Meng, Xiang-Min
Abstract : Orthorhombic SnSe nano-plates possess strong angle-resolved Raman property and obvious in-plane anisotropic photo-response, which could be used in creation of new-type devices and to supplement experimental results in study of anisotropic properties. Abstract : In-plane anisotropy in optical, electronic and thermal properties of two-dimensional (2D) materials has attracted significant interest because of the huge potential applications for developing novel devices. In this work, outstanding angle-dependent Raman property of layered SnSe nano-plates is obtained via polarized Raman system and it is confirmed that the Raman polarization directions of two Ag modes (130 cm −1 and 150 cm −1 ) are consistent with specific crystalline directions (zigzag direction or armchair direction) of SnSe flakes under parallel polarization configuration at home temperature and low temperature. Furthermore, the SnSe nano-plate devices show excellent angle-resolved photo-response at home temperature and low temperature (150 K) with a 90° cycle period and the polarized directions are also along zigzag direction and armchair direction, which is ascribed to the unique in-plane asymmetric crystal structure. These prominent in-plane anisotropic properties provide a precise and rapid method to determine the crystal orientation of SnSe nano-flakes and open up the new applications of 2D asymmetric structure materials.